2021
DOI: 10.3389/fmicb.2021.750489
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm Formation in Methicillin-Resistant Staphylococcus aureus Isolated in Cystic Fibrosis Patients Is Strain-Dependent and Differentially Influenced by Antibiotics

Abstract: Cystic fibrosis (CF) is a genetic disease with lung abnormalities making patients particularly predisposed to pulmonary infections. Staphylococcus aureus is the most frequently identified pathogen, and multidrug-resistant strains (MRSA, methicillin-resistant S. aureus) have been associated with more severe lung dysfunction leading to eradication recommendations. Diverse bacterial traits and adaptive skills, including biofilm formation, may, however, make antimicrobial therapy challenging. In this context, we c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 63 publications
0
15
0
Order By: Relevance
“…A publication by Henriksen et al described this molecule as a good potential therapeutic treatment, since all the clinical strains isolated in this study had very low MICs [ 64 ]. However, no study in the literature mentions the potential antibiofilm effect of ceftobiprole on CoNS, despite its efficacy against S. aureus [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…A publication by Henriksen et al described this molecule as a good potential therapeutic treatment, since all the clinical strains isolated in this study had very low MICs [ 64 ]. However, no study in the literature mentions the potential antibiofilm effect of ceftobiprole on CoNS, despite its efficacy against S. aureus [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…Next, we profiled the phenotypic traits that reflect the metabolism and/or virulence of these MRSA isolates. These traits include biofilm formation and carotenoid pigment production, where biofilm facilitates MRSA colonization in CF lungs, and pigmentation has been linked to virulence ( 16 18 ). Colorimetric analysis revealed that 20% of the isolates generated more biofilm matrix compared to a previously identified biofilm-producing strain ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As compared to vancomycin, a frontline antibiotic for treatment of MRSA infections, anthracimycin was 60 times more potent. This result is significant because the MRSA biofilm formation [48][49][50][51] is primarily responsible for the reduced efficacy or inefficacy of many clinically used antibiotics for MRSA infections, and anthracimycin demonstrated the potential as a new effective anti-MRSA antibiotic.…”
Section: Resultsmentioning
confidence: 99%